Pengaruh Fasilitas Kantor, Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja : Studi Pada Petugas Teknis Kesehatan Hewan - Imanuel Yahya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The background of this research is that the performance of field technical officers at the Animal Husbandry and Fisheries Service is still not optimal. The contributing factors are office facilities, work motivation and work discipline of Animal Health Technical Officers which also do not support performance implementation. Thus, the purpose of this study was to find out and describe office facilities, work motivation and work discipline on the performance of Animal Health Technical Officers. The method used is quantitative descriptive with the results of the study showing that office facilities have a positive and significant effect on the performance of Animal Health Technical officers. This means that if the office facilities increase, it will be followed by an increase in the performance of Animal Health Technical officers. work motivation has a positive and significant effect on the performance of Animal Health Technical officers. This means that if work motivation increases, it will be followed by an increase in the performance of Health Technical officers. Work discipline has a positive and significant effect on the performance of Animal Health Technical officers. This means that if work discipline increases, it will be followed by an increase in the performance of Animal Health Technical officers. Office facilities, work motivation and work discipline have a positive and significant effect on the performance of Animal Health Technical Officers. This means that if office facilities, work motivation and work discipline increase, it will be followed by an increase in the performance of Animal Health Technical officers